Foreign workers' health in agriculture: assessing health workers' perception and training needs. (13th November 2019) - Salvatori, L M; Rinaldi, A; Angelozzi, A; Caminada, S; Paglione, L; Persechino, B; Marceca, M
Abstract: Introduction: Health and safety of foreign workers employed in agriculture and zootechny present several critical areas. The multidisciplinary project 'Livingstone', funded by INAIL and carried out by several Italian universities, aims to address some of these critical issues. One of the project research line focuses on health professionals and has the objective to investigate their perception of the risks to which foreign workers are exposed and their training needs. Methods: A 33 items questionnaire is being self-administered to social and health professionals of three Italian regions (Lazio, Lombardia and Campania) where agriculture is developed; the administration phase will last 13 months (2018, April - 2019, May). The questionnaire has been built starting from a literature review; a pilot study have been conducted in a pilot sample in Rome in March 2018. The questionnaire is composed by five sections: general, social and professional information; characteristics of the respondents' foreign patients/users; knowledge about health problems of foreign patients and about possible obstacles in use of health services, with a specific focus on foreign patients working in agriculture and zootechny sector; perception about health and safety risks of these workers; training background and needs, included desired training contents and modalities. Results: The research is ongoing. 238 answered questionnaires have been collected yet. 65 of the respondents are General Practitioners; the rest are other health and social professionals. The complete results will be shown during the congress. Conclusions: This study will contribute to widen the knowledge about health professionals' perceptions about problems and needs of foreign workers employed in agriculture and zootechny sector. Specific training addressed to social and health professionals will be developed from the observation of their current knowledge and from their reported needs. Key messages: This study will contribute to widen knowledge about health professionals' perceptions about problems and needs of foreign workers employed in agriculture and zootechny sector. Specific training addressed to social and health professionals will be developed from the observation of their current knowledge and from their reported needs.